Entrepreneurial threads: the transformative impact of Tiktok on fashion industry dynamics - Omar Ali, Siti Rapidah (Universiti Teknologi MARA, Terengganu, 2024)
Social media specially fashion media, appears to be consolidating its power structure and attempting to take over public spheres to increase its influence. Social media, utilizing advanced algorithms and emotional marketing, is shifting away from traditional marketing methods focused on the commodity supply chain. Instead, it targets consumer emotions in both public and private settings.